(untitled) (A Text Book of Pharmaceutics for I Year Diploma in Pharmacy, 2024)
Author: Mr. Anilkumar Vadaga Associate Professor, GIET School of Pharmacy, Rajahmundry, Andhra Pradesh, India Abstract: Pharmaceutical aids, also known as excipients, are essential components in drug formulations that serve various functions beyond the active pharmaceutical ingredient (API). These substances play crucial roles in enhancing the stability, bioavailability, manufacturability, and patient acceptability of medicinal products. Common categories of pharmaceutical aids include diluents, binders, disintegrants, lubricants, glidants, and preservatives. Each type of excipient contributes uniquely to the overall performance of the dosage form. For instance, diluents provide bulk to small-dose drugs, while binders ensure tablet cohesion. Disintegrants facilitate the break-up of solid dosage forms in the gastrointestinal tract, enhancing drug release. The selection of appropriate pharmaceutical aids is a critical aspect of formulation development, requiring consideration of drug-excipient compatibility, stability, and regulatory compliance. Recent advancements in excipient technology have led to the development of multifunctional excipients and those derived from natural sources, addressing the growing demand for improved drug delivery systems and environmentally friendly options. Keywords: Excipients, Formulation, Drug delivery, Stability, Bioavailability, Multifunctional aids View PDF